Trunk muscle behaviors during the full-cycle stoop and squat lifting tasks - Fumin Pan; Wei Wang; Chao Kong; Shibao Lu (PeerJ, 2025)
Background Lifting is generally considered as a risk factor for low back pain. A thorough investigation of the muscle function during lifting is essential for a better assessment of the potential risk of muscle impairment and towards improvements in lifting strategy. We aimed to compare the activities of the trunk muscles between the stoop and the squat lifting tasks. Methods A surface electromyography device was used to measure the muscle activity during the full-cycle squat and the stoop lifting tasks of a 5-kg weight. Each task was divided into four stages: stage 1 was bending forward to reach the weight, stage 2 was lifting the weight up, stage 3 was lowering the weight down, and stage 4 was returning to the upright position. The maximum electromyographic (EMG) activities among different tasks and different stages were compared. Eighteen males aged 20–35 years without low back pain were included, with a mean age of 26.55 ± 2.12 years, body height of 175.18 ± 4.29 cm, body weight of 69.27 ± 4.29 kg, and BMI of 22.56 ± 0.87 kg/m2. Results During stoop lifting, the median values of the absolute EMG of the left multifidus were 53.96, 70.32, 51.08 and 64.14 uV from stage 1 to stage 4, which were all non-significantly lower than those during squat lifting for 79.84, 103.64, 71.72 and 95.72, respectively (P > 0.05). The absolute EMG was greatest during stage 2, then during stage 4, stages 1 and 3 came next (Effect size = 0.879, P < 0.001). The median values of the normalized EMG of each muscle during stoop lifting were also non-significantly lower than those during squat lifting at each stage (P > 0.05). The normalized EMG was also greatest during stage 2, then during stage 4, and was lowest during stages 1 and 3 (Effect size = 0.932, P < 0.001). Conclusion The trunk muscles were similarly activated during squat and stoop lifting. During lowering the weight down, the trunk muscles were less activated than during extension to the upright position without weight in hands. These results could help to develop subject-specific strategies for lifting tasks to prevent or alleviate occupational low back pain.